THE INFLUENCE OF DOW JONES ISLAMIC MARKET, WORLD GOLD PRICE AND INFLATION ON JAKARTA ISLAMIC INDEX FROM JANUARY 2008 to SEPTEMBER 2013 - Egan Janitra (2014)
This study aims to analyze the influece of Dow Jones Islamic Market, world gold price and inflation towards the Jakarta Islamic Index (JII) in Indonesia Stock Exchange (IDX) from January 2008 to September 2013. The object of the study is publicly traded company listed on the Jakarta Islamic Index (JII). Data are obtained from Bank Indonesia site, Yahoo!! Finance, Google Finance, Kitco Gold Historical Price and HOTS KDB Daewoo securities. The obtained index is 30 companies listed in Jakarta Islamic Index (JII) with 69 observation data. Data analysis is performed using Error Correction Model (ECM). The result shows that whole variables have significant influence toward Jakarta Islamic Index in the long run. While in case of short run, Dow Jones Islamic Market has a significant influence toward Jakarta Islamic Index, but world gold price and inflation are not. Keyword: Jakarta Islamic Index, Dow Jones Islamic Market, World Gold Price, Inflation, Error Correction Model.